(untitled) (Bangladesh Journal of Medical Microbiology, 2009)
Fourth Edition, September-2008 ISBN 984-31-0195-7 Authors: Professor Dr. Md. Akram Hossain Dr. Md. Abul Hossain Khan Published by: Aanisha Publication, 62, Bagmara, Mymensingh 220 Pages: 488 Price: 350/-